An observational study of association of thyroid dysfunction and heart failure in a tertiary care centre - Hiremath, Anjali; Barge, Vijay; Bafna, Varun; Paritekar, Anita (International Journal of Research in Medical Sciences, 2024)
Background: Heart failure (HF) is becoming leading problem in world now a days. Thyroid hormone has been proven to influence physiologic functions of cardiovascular system in many ways. HF presents a clinical challenge, with thyroid dysfunction emerging as a significant comorbidity, affecting prognosis and management. Approximately 22% of patients with HF have been demonstrated to have thyroid dysfunction. Clinical studies were confirmed that the patients with sub-clinical hypothyroidism had high risk of cardiovascular disease due to increased low density lipoprotein, elevated homocystein, hypercoagulative blood. In this study, we aim to evaluate association between sub-clinical hypothyroidism and HF to know its clinical significance. Methods: An observational study conducted over three months on 70 diagnosed HF patients admitted in tertiary care hospital, evaluating history, clinical profile and demographics, HF types, comorbidity, and screened for thyroid function. Results: Thyroid dysfunction prevalence among HF patients was 27.14%, with subclinical hypothyroidism being most common. Treatment led to significant improvements in symptoms and cardiac function. Conclusions: There is significant correlation between thyroid dysfunction and HF with Subclinical hypothyroidism can be independent risk factor for HF. Timely and early recognition and management of thyroid dysfunction in HF patients are crucial for prognosis enhancement. Early intervention holds promise for improved outcomes in HF management.